Atypical Presentation of Left Hepatic Artery Pseudoaneurysm. Issue 7 (1st July 2022) - Niaz, Murk; Khan, Muhammad Arsalan; Muhammad, Shah; Khan, Abdaal Waseem
ABSTRACT: Hepatic artery pseudoaneurysm (HAP) commonly occurs after trauma and is rarely seen as a complication of pyogenic liver abscess. Patients with HAP can present with hemobilia secondary to arterobiliary fistula. We report a case of a 29-year-old woman who presented with abdominal pain, fever, and jaundice, who was diagnosed to have a pyogenic liver abscess that had led to the development of left HAP, presenting with hemobilia. The patient was successfully managed with endovascular coil embolization.